Biomechanical analysis of sub-elite performers in the women's long jump - Panoutsakopoulos, V.; Kollias, I. (New Studies in Athletics, 2007)
Biomechanical analysis of sub-elite competitions enriches the pool of knowledge about technique in athletics events. The purpose of this study was to describe the kinematics of the approach and take-off of competitors in the women's long Jump competition at the 2006 European Cup 1st League-Group B. It was found that all the participants utilise the "longer penultimate-shorter last stride" ratio previously described for top-level performers. All but one increased their horizontal velocity during the last stride. Mean horizontal and vertical take-off velocities were 8.71m/sec (Standard deviation: 0.26) and 2.45m/sec (0.12) respectively, resulting in a mean take-off angle of projection of 18.1 degrees (0.7). The values of the selected biomechanical Parameters were either in range (i.e. loss of horizontal velocity during contact with the board, energy loss in take-off) or lower (i.e. take-off velocity, angle of projection) than results obtained at higher-level events such as the World Championships or Olympic Games.